Implementasi Kompetensi Akademik dan Manajerial Pada Lembaga TPQ (Studi Kasus di TPQ Mamba’ul ‘Ulum) - Az Zahra Nabila Rofi’ah; Maryono Maryono; Salis Irvan Fuadi (Pusat Riset dan Inovasi Nasional, 2023)
The competence possessed by a teacher is very important for the continuity of an educational institution. Moreover, seeing the development of education today, teacher professionalism is needed not only in academic competence but also in managerial competence in managing institutions to achieve institutional educational goals. The objectives of this study are 1) To find out how the efforts made by teachers to improve their academic and managerial abilities at the TPQ Mamba'ul 'Ulum institution 2) To find out how the description of the academic and managerial competencies of institutions in the context of utilizing Human Resources (HR) in TPQ Mamba'ul 'Ulum institution 3) To find out what challenges and obstacles are faced by teachers in implementing academic and managerial competencies at TPQ Mamba'ul 'Ulum institutions. Based on the results of this study, it can be concluded that efforts to increase the academic and managerial competence of teachers in institutions are carried out with the discipline of evaluating, developing knowledge and insight, and participating in teacher training. The description of academic and managerial competencies in the institution involves all components in the institution starting from implementing the regulations from the qiraati method coordinator who oversees the running of the institution and teacher professionalism. The challenge faced by the Institute is to keep up with the times which are aligned with the progress of teacher competence, while the obstacles experienced are the lack of teaching staff who are the main factor in the success of an educational institution.